Deoxygenation effect on hydrophilicity changes of Shengli lignite during pressurized pyrolysis at low temperature - Huang, X.; Zhang, Shu; Lin, X.; Wang, Y.; Xu, M. (2013)
The effect of temperature (200~350 °C) and pressure (0.25~8.00 MPa) on the elimination of main oxygen-containing functional groups of Shengli lignite was examined during pyrolysis in a fixed-bed reactor. Effects of the reduction of oxygen-containing functional groups on the moisture holding capacity (MHC) of coal samples were also investigated. The results showed that temperature was the key factor on the removal of carboxyl and phenolic hydroxyl from the lignite. The variation of pressure had few effects on the removal of carboxyl in coal; in contrast, phenolic hydroxyl was reduced to a minimum point at the pressure between 3.00 to 4.00 MPa. The carboxyl content in the lignite played a dominant role on the surface polarity and moisture holding capacity. The influence of specific surface area on the MHC became distinct when the carboxyl content in coal samples kept constant.